La migración Centroamericana a Estados Unidos y los laberintos del desarrollo - Torres Rivas, Servicio Jesuita para Migrantes de Centroamérica (Revista Española de Desarrollo y Cooperación, 2023)
This article focuses on remittances but it starts by underscoring the ambivalence of migration in relation to development. Remittances are often presented as a productive opportunity. They are, in fact, a strategy put in practice by workers that ends up being co-opted by transnational corporations. In Central America, they encourage cosumption based on migrants’ transnational savings.